Competition Law Perspective on The Assessment of Conglomerate Merger in Indonesia (Case Study: PT. Aplikasi Karya Anak Bangsa (Gojek) with PT. Tokopedia) - Varial Ashari Djafar (LEGAL BRIEF, 2022)
This study examines conglomerate merger arrangements about monopoly practices and fair business competition in Indonesia conducted by PT. Aplikasi Karya Anak Bangsa and PT. Tokopedia uses a juridical-normative method with a descriptive research type, and research data is collected through secondary data consisting of legal materials. The results of this study are that KPPU as the authority that has the authority to supervise and examine business competition cases in Indonesia, made Commission Regulation Number 3 of 2019 concerning the Assessment of Mergers or Consolidations of Business Entities, or Acquisition of Company Shares Which May Lead to Monopolistic Practices and/or Unfair Business Competition and Guidelines for Evaluation of Mergers, Consolidations and Acquisitions issued and promulgated on October 6, 2020. The KPPU does not apply the theory of potential competition to this assessment. The Assessment Method for Conglomerate Mergers in Indonesia in current laws and regulations has not yet applied the potential competition theory which can predict market conditions that will occur in the future so that the Merger of PT. GoTo has the potential to create a data monopoly because Gojek and Tokopedia services are practically connected vertically so that it can strengthen the ecosystem of PT. GoTo. The advantage of having an assessment of mergers that eliminates potential entrants as has been implemented by the United States, where the competitive law enforcement authorities there can predict market conditions that will occur in the future if a merger is carried out or not carried out. This research suggests that the Business Competition Supervisory Commission should carry out intensive and strict supervision of PT. GoTo in the future and should in evaluating conglomerate mergers, especially in the digital market, apply the potential competition theory to minimize the potential for competitive behavior from giant companies merging in Indonesia.